Cxcr1 gene snp variability that affects mastitis resistance in holstein cows in türkiye - Kozet AVANUS; Alper YILMAZ; Halil GÜNEŞ; Ahmet ALTINEL; Bülent EKİZ; Hülya YALÇINTAN; Dilara KEÇİCİ; Nurşen DOĞAN (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Genotyping 16 SNPs of C-X-C motif chemokine receptor 1 (CXCR1) gene region which affects host resistance against mastitis disease was carried out in Holstein cows raised in Türkiye. In this study, the frequency of the undesirable C allele in the CXCR1 c.771C>G polymorphic region, associated with an incomplete response, was found to be high. Additionally, the genotypes c.1016AA and c.1016GG, which contribute to mastitis resistance, were observed at low frequencies. Several SNP loci in the CXCR1 gene, including c.606G>A, c.678G>A, c.1104G>A, c.1119+6C, c.1119+7A, and c.1119+10, significantly deviated from Hardy-Weinberg equilibrium (HWE) (P<0.0001), indicating violations of HWE assumptions such as random mating and absence of selection. The deviations at c.606G>A, c.678G>A, and c.1104G>A suggest strong selection pressures, likely due to artificial selection in Holstein cattle. These variants are synonymous mutations that do not alter the amino acid sequence but may influence protein synthesis through effects on mRNA stability, splicing, or translation efficiency. Furthermore, the absence of heterozygotes at loci c.1119+6C, c.1119+7A, and c.1119+10, which are located on untranslated regions (UTRs), potentially affecting gene expression by regulating mRNA stability, localization, or translation initiation, points to genetic drift or population substructure. These findings are important for understanding genetic variability and can inform marker-assisted selection programs to enhance breeding strategies while preserving genetic diversity for traits like disease resistance and milk production.